SISTEM PEMBAYARAN CASH ON DELIVERY TERHADAP KEPUTUSAN PEMBELIAN DI SHOPEE - Sudung Simatupang; Desi Susanti; Marisi Butarbutar; Kevin Indajang; Rosita Manawari Girsang (JURNAL ILMIAH EDUNOMIKA, 2024)
The development of digital technology has made the business world provide more innovative services in reaching a wider range of consumers, one of the systems that is expected to support these efforts is the Cash On Delivery (COD) service with the hope that it can support purchasing decisions. The results of the study found that there is a positive direction coefficient from Cash On Delivery on purchasing decisions, with the ability to explain Cash On delivery to purchasing decisions worth a strong correlation (R). The partial hypothesis test (Test) t shows a positive and significant effect of the Cash On Delivery variable on purchasing decisions. This means that Cash On Delivery is able to support the decision of consumers to make purchases when these consumers do not have a digital payment system, such as mobile banking, shoope pay, funds and so on.